A Comparative Study of Structural and Functional Changes of Female-Headed Households in Rural Areas in Sri Lanka - W.M.G.N. Panampitiya (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: Male-Headed Households (MHHs) and Female-Headed Households (FHHs) can be distinguished by the gender of the household’s primary breadwinner. Male heads of households are the norm in patriarchal societies. However, there are many situations in which a woman must take on the headship role on her own: when her husband dies, gets sick or disabled, leaves her, gets divorced, never marries, etc. Thus, this research aims to compare how FHHs were set up before and after women took charge. Methodology: This research was carried out in the Kurunegala district of the North-Western province of Sri Lanka in the five Grama Niladari divisions of the Galgamuwa divisional secretariat: Molewa, Kallanchiya, Koonw ewa, Wadugama, and Medawachchiya. Purposive sampling was used to select 100 female participants with FHHs verification. Questionnaires and semi-structured interviews were the primary methods of data collection. Surveys and case studies were employed in the study’s research. Descriptive statistics were used to examine the numbers, while the descriptive approach was used to investigate the qualitative information. Findings: Changes to FHHs are more dramatic when one or both parents move back in with their children when a child moves back in with a different guardian, when a child marries and leaves the reproductive family, when a child dies, or when a child becomes an ordained religious leader. The study focused on how the household’s economic role and decision-making authority have changed. Implications/Novel Contribution: Seventy-four percent of women in leadership roles feel that structural and functional changes have negatively impacted their lives. Several factors, including economic hardship, insecure livelihood activities, sole household responsibilities, a lack of supportive community mechanisms, gender bias in the socialization process, dependency and a subordinate mentality in decision- making, and other factors, have influenced their adverse reactions to specific functional changes after assuming the headship. Therefore, it is essential to run mobilization and empowerment programs for women heads at the grass-roots level to boost their decision-making, leadership, and active community engagement potentials. We must provide emotional support systems like therapy, mentoring, and advocacy to enhance their mental health. The study brings key policy insights for social scientists and gender studies scholars.